Hydrogen For Mobility a Zero Carbon Transportation System (Global Journals of Research in Engineering, 2024)
Eliminating hydrocarbon transportation must be a fundamental goal for society if we are to negate Climate Change and its consequences No source of CO2 emissions comes close to that of hydrocarbon fueled internal combustion engines and if we are to transition to a zero-carbon energy system a viable alternative to hydrocarbon fuels must be found Lithium-Ion powered vehicles or EV s present society with a paradox they emit zero emissions however the life cycle of Lithium-Ion batteries is a source of environmental concern through mining deforestation of carbon sinks the immense electrification requirements for battery production recycling and recharging This communication proposes Hydrogen for Mobility as the future fuel for a pathway to a Zero Carbon Transportation System through utilizing both the existing internal combustion engine ICE and most existing transportation infrastructure at the same time being cost effective efficient and zero emitting An overview of technologies will be discussed along with their Technology Readiness benefits and issues This discussion expands on the concepts discussed in Mobile Modular Hydrogen Power Generation a Zero Carbon Energy System https doi org 10 5296 ijgs v7i1 xxxx
Keywords: hydrogen; biofuel; fuel cell; electric; mobility; engine; vehicle; emissions